Analysis of Factors Influencing the Purchase Intention of Online Auction Consumers on Facebook (Journal of Innovation, Business and Entrepreneurship, 2020)
According to DilelangAja - an online auction service provider currently operating on Facebook - online auction’s rate of sales fluctuates with few studies having researched the cause of this, particularly Indonesian online auctions. The purpose of this research is to discover the factors which influence online auction customer’s purchase intentions and determine the best solution to apply the newfound knowledge to DilelangAja and similar services. The data collection method for this study was through an online survey, consisting of quantitative questions with Likert scaled-answers. The respondents of this survey were 150 members of various hobby communities on Facebook in the same market as DilelangAja with the sampling method using the non-probability judgmental method. Descriptive statistics along with partial least squares structural equation modeling (PLS-SEM) were used to analyze the data gathered from the online survey. It was found that the perceived product and service quality and perceived convenience are the most influencing independent variables to the purchase intention, through the perceived ease of use and usefulness. For DilelangAja, the recommendations from the findings are focusing improvements on product quality, service quality, and the convenience of the auction.Keywords: E-commerce, online auction, DilelangAja, Facebook, purchase intention, PLS-SEM